N-(3-Chloro-4-fluorophenyl)acetamide - Fun, Hoong-Kun (International Union of Crystallography, 2012)
In the title compound, C(8)H(7)ClFNO, the dihedral angle between the benzene ring and the acetamide side chain is 5.47 (6)°. An S(6) ring motif is formed via an intramolecular C—H⋯O hydrogen bond. In the crystal, N—H⋯O hydrogen bonds link the molecules into C(4) chains along [001].